Optimizing Local Museum as a History Learning Medium: A Case Study in Central Sulawesi - Suyuti Suyuti (STAI Hubbulwathan Duri, 2022)
This research was conducted to explore the function and role of the Museum in Central Sulawesi to be used as a medium for learning history. This qualitative study used a case study as the method. The data were obtained from observation to the field and analyzed using content analysis. The results of this study at the Museum of Central Sulawesi show that the readiness of human resources has not been maximized, the management and support system for audiovisual equipment that only used two workers were still very simple, efforts to increase the audio-visual space were still limited to socialization, the concept of the audio-visual room did not involve sufficient officers with a complete and integrated management system and did not follow the development of information technology and computer technology. As a conclusion, it is important to upgrade the facilities of the Museum in Central Sulawesi to optimize the use of this place as a medium for learning history.